Development of E-Module-based Civics Teaching Materials on Human Rights Materials to Improve Students' Learning Motivation in Class XI SMAN 2 Muaro Jambi: Development of E-Module-based Civics Teaching Materials on Human Rights Materials to Improve Students' Learning Motivation in Class XI SMAN 2 Muaro Jambi - Silmaika, Ema; Irwan, Irwan; Sariani, Dona (Citizenship Education, Faculty of Education, Jambi University, 2022)
This research was motivated by the existence of problems at SMAN 2 Muaro Jambi, namely the low learning motivation of students in Class XI IPA 3 SMAN 2 Muaro Jambi. Then the teacher has difficulty in developing teaching materials that can make students interested in learning.The purpose of this research is to develop E-Module-based Civics Education teaching materials on human rights materials and to increase student motivation in class XI SMAN 2 Muaro Jambi.This research is a development research and uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. This study develops Civics teaching materials by giving tests to determine students' learning motivation. The instruments used in this study were a questionnaire on the assessment of material experts, media experts, and linguists, teacher and student responses and student learning motivation questionnaires.Based on the results of research conducted by providing a student learning motivation questionnaire at the end of the learning activity, 28 students were found whose learning motivation increased with a percentage of 81.7% KeywordS : Motivation, e-Module, Human Rights